2013
DOI: 10.1093/geront/gnt018
|View full text |Cite
|
Sign up to set email alerts
|

Korea: Balancing Economic Growth and Social Protection for Older Adults

Abstract: Population aging in Korea is projected to be the most rapid among Organisation for Economic Co-operation and Development (OECD) countries between 2000 and 2050. However, social spending in Korea remains low, reflecting Korea's relatively young population, limited health and long-term care insurance coverage, and immaturity of its pension system. As these factors evolve in coming years, social spending in Korea is likely to rise toward the OECD average. Sustaining economic growth requires policies to mitigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 3 publications
0
40
0
Order By: Relevance
“…With increasing awareness of Long‐Term Care Insurance, the proportion of older adults who have applied for benefits reached 12.3% in 2010, with 45.9% deemed to be eligible. Because of limited coverage and immaturity of Long‐Term Care Insurance, the proportion of older adults receiving benefits was 4.4% in 2010, and the findings reflect this lack of usage of the governmental program …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing awareness of Long‐Term Care Insurance, the proportion of older adults who have applied for benefits reached 12.3% in 2010, with 45.9% deemed to be eligible. Because of limited coverage and immaturity of Long‐Term Care Insurance, the proportion of older adults receiving benefits was 4.4% in 2010, and the findings reflect this lack of usage of the governmental program …”
Section: Resultsmentioning
confidence: 99%
“…While out‐of‐pocket payments might discourage frivolous demands and limit costs, they can hardly care for catastrophic or chronic illness, and for those unable to afford even modest copayments. In addition to penalizing low‐income households, out‐of‐pocket payments create a substantial burden on those with chronic health problems, such as older adults with cancer …”
Section: Discussionmentioning
confidence: 99%
“…Our subgroup analysis confirmed that receipt of national pension benefits was associated with QoL among individuals with low levels of income or wealth. Although we know of no previous research examining the relationship between national pension receipt and QoL among retired elderly Koreans, many reports emphasize the importance of national pensions for older adults …”
Section: Discussionmentioning
confidence: 99%
“…Pensionable ages were adjusted from 60 to 61 years‐of‐age in 2013, and will increase by 1 year every 5 years until the retirement age reaches 65 years in 2033 . Nevertheless, the NPS is expected to record a deficit in 2044 and to reduce its benefits in response to an increase in spending that is projected to exceed the increase in revenue . Thus, the pension system in Korea might need to be further reformed in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…LTCI primarily covers social care services, with a focus on providing support for those who need lifetime assistance with daily activities, regardless of their income level. Since its inception, long‐term care (LTC) services have been successfully offered to older adults with severe functional limitations, and the coverage rate in the Korean population increased from 1.4% in 2008 to 7.5% in 2016 . There was a three‐level eligibility system under the Korean LTCI.…”
Section: Introductionmentioning
confidence: 99%